PENGARUH PENERAPAN TEKNIK BISNIS BERISIKO TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS IX SMPN 25 PADANG TAHUN PELAJARAN 2013/2014 - Mariska, Widya; Rismen, Sefna; Husna, Husna (Pendidikan Matematika, 2013)
This research is motivated by the students math concept comprehension and a sense of responsibility of the studentâs exercises are still low. The aims of this research to look at how the development of studentâs activity by applying Teknik Bisnis Berisiko to determine whether students math concept comprehensionby applying Teknik Bisnis Beresiko is better than student math concept comprehension by applying conventional learning. The type of research is experimental, population is all student in grade IX SMPN 25 Padang school year 2013/2014. Technique that is used is random sampling. The instrument used in this research was the observation sheet and final test math concept comprehension. Data analysis activities performed byc alculating the percentage of students, the results showed that the students activity has increased. The result of Hypothesis test by using t-test one part with the Minitab Software obtained t>tÎ±. It means that the hypothesis in this research is accept, so it can be concluded that the students math concept comprehension by applying Teknik Bisnis Berisiko is better than the students math concept comprehension by applying conventional learning class IX SMPN 25 Padang school year 2013/2014 .